Contaminant Emissions as Indicators of Chemical Elements in the Snow Along a Latitudinal Gradient in Southern Andes - Vergara-Egert, P; Castillo-Castillo, X; Cordero-Carrasco, R; Pizarro-Reyes, J; Pizarro-Reyes, J; Damiani, A; Rowe, P; Llanillo, P (Nature Research, 2021)
The chemical composition of snow provides insights on atmospheric transport of anthropogenic contaminants at different spatial scales. In this study, we assess how human activities influence the concentration of elements in the Andean mountain snow along a latitudinal transect throughout Chile. The concentration of seven elements (Al, Cu, Fe, Li, Mg, Mn and Zn) was associated to gaseous and particulate contaminants emitted at different spatial scales. Our results indicate carbon monoxide (CO) averaged at 20 km and nitrogen oxide (NOx) at 40 km as the main indicators of the chemical elements analyzed. CO was found to be a significant predictor of most element concentrations while concentrations of Cu, Mn, Mg and Zn were positively associated to emissions of NOx. Emission of 2.5 μm and 10 μm particulate matter averaged at different spatial scales was positively associated to concentration of Li. Finally, the concentration of Zn was positively associated to volatile organic compounds (VOC) averaged at 40 km around sampling sites. The association between air contaminants and chemical composition of snow suggests that regions with intensive anthropogenic pollution face reduced quality of freshwater originated from glacier and snow melting. © 2021, The Author(s).